Fish ponds as a factor of development in rural areas of Bosnia and Herzegovina - Nurković, Rahman (Journal for Geography, 2014)
This paper explains the impact of fish farms on the development of rural areas in Bosnia and Herzegovina. Fishing in Bosnia and Herzegovina was recognized as an opportunity for industrial production, tourism and placing high quality healthy food on market as well as rural development and the possibility of creating new jobs. In terms of agroclimatic conditions, Bosnia and Herzegovina has a very favorable geographical, hydrological, climatic and ecological conditions for fish production, which is reflected in the availability of water resources of rivers, lakes and marine fish farms. In Bosnia and Herzegovina there are 41 registered fish farms of freshwater and saltwater fish and it is estimated that there are about twenty unregulated fish farms. With the available resources, the existance of tradition in production, decades of existance of lake fish ponds and dynamic development of production in cages classify fish farming as a significant branch of economy, which ensures it in the domestic market, but also on the markets of neighboring countries, the European Union.